2022
DOI: 10.3390/medicina58030433
|View full text |Cite
|
Sign up to set email alerts
|

Serum NfL in Alzheimer Dementia: Results of the Prospective Dementia Registry Austria

Abstract: Background and Objectives: The neurofilament light chain (NfL) is a biomarker for neuro-axonal injury in various acute and chronic neurological disorders, including Alzheimer’s disease (AD). We here investigated the cross-sectional and longitudinal associations between baseline serum NfL (sNfL) levels and cognitive, behavioural as well as MR volumetric findings in the Prospective Dementia Registry Austria (PRODEM-Austria). Materials and Methods: All participants were clinically diagnosed with AD according to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Three studies conducted both cross‐sectional and longitudinal analyses on the association between neuropsychiatric symptoms and blood‐based biomarkers. A study from Austria showed associations between serum NfL and neuropsychiatric symptoms in cross‐sectional but not longitudinal analyses among 237 AD patients 45 . In contrast, research from the United States failed to establish cross‐sectional associations between plasma levels of Aβ42 or Aβ42/Aβ40 and depression, but low Aβ42/Aβ40 at baseline was associated with an increased risk of developing depression after 9 years of follow‐up in APOE Ɛ4 carriers but not in non‐carriers 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies conducted both cross‐sectional and longitudinal analyses on the association between neuropsychiatric symptoms and blood‐based biomarkers. A study from Austria showed associations between serum NfL and neuropsychiatric symptoms in cross‐sectional but not longitudinal analyses among 237 AD patients 45 . In contrast, research from the United States failed to establish cross‐sectional associations between plasma levels of Aβ42 or Aβ42/Aβ40 and depression, but low Aβ42/Aβ40 at baseline was associated with an increased risk of developing depression after 9 years of follow‐up in APOE Ɛ4 carriers but not in non‐carriers 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Austria showed associations between serum NfL and neuropsychiatric symptoms in cross‐sectional but not longitudinal analyses among 237 AD patients. 45 In contrast, research from the United States failed to establish cross‐sectional associations between plasma levels of Aβ42 or Aβ42/Aβ40 and depression, but low Aβ42/Aβ40 at baseline was associated with an increased risk of developing depression after 9 years of follow‐up in APOE Ɛ4 carriers but not in non‐carriers. 24 Furthermore, a population‐based cohort study among 980 older adults revealed conflicting findings—that is, persons with high Aβ40 levels had more clinically relevant depressive symptoms in cross‐sectional analyses at baseline, whereas in longitudinal analyses, persons with low levels of Aβ40 and Aβ42 had a higher risk of developing clinically relevant depressive symptoms over a mean follow‐up of 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Using ultrasensitive single-molecule array assays (Simoa), it is possible to measure low concentrations of NfL, not only in the CSF but also in blood samples, with very high sensitivity. In this prospective study of patients with AD conducted by Kern et al [ 5 ], higher sNfL concentrations were associated with worse cognitive performance, and there were no significant associations with respect to changes in neuropsychiatric symptoms and volumes of the brain regions typically affected by AD pathology.…”
mentioning
confidence: 91%
“…5 Concomitantly, changes in sNfL have been shown to correlate with disease progression in several other neurological diseases including Parkinson's disease, Alzheimer's disease, Huntington's disease, and traumatic brain injury. 6,7 There is also a growing body of studies of sNfL ª 2024 The Authors. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, changes in sNfL have been shown to correlate with disease progression in several other neurological diseases including Parkinson's disease, Alzheimer's disease, Huntington's disease, and traumatic brain injury. 6 , 7 There is also a growing body of studies of sNfL in non‐neurological settings. sNfL was increased in COVID‐19 patients on mechanical ventilation, and associated with unfavorable outcomes.…”
Section: Introductionmentioning
confidence: 99%